Advancing interprofessional education through the use of high fidelity human patient simulators - Kane-Gill SL; Smithburger PL; Kloet MA; Lohr B; Seybert AL (Centro de Investigaciones y Publicaciones Farmaceuticas, 2013)
Background: Modern medical care increasingly requires coordinated teamwork and communication between healthcare professionals of different disciplines. Unfortunately, healthcare professional students are rarely afforded the opportunity to learn effective methods of interprofessional (IP) communication and teamwork strategies during their education. The question of how to best incorporate IP interactions in the curricula of the schools of health professions remains unanswered.Objective: We aim to solve the lack of IP education in the pharmacy curricula through the use of high fidelity simulation (HFS) to allow teams of medical, pharmacy, nursing, physician assistant, and social work students to work together in a controlled environment to solve cases of complex medical and social issues.Methods: Once weekly for a 4-week time period, students worked together to complete complex simulation scenarios in small IP teams consisting of pharmacy, medical, nursing, social work, and physician assistant students. Student perception of the use of HFS was evaluated by a survey given at the conclusion of the HFS sessions. Team communication was evaluated through the use of Communication and Teamwork Skills (CATS) Assessment by 2 independent evaluators external to the project.Results: The CATS scores improved from the HFS sessions 1 to 2 (p = 0.01), 2 to 3 (p = 0.035), and overall from 1 to 4 (p = 0.001). The inter-rater reliability between evaluators was high (0.85, 95% CI 0.71, 0.99). Students perceived the HFS improved: their ability to communicate with other professionals (median =4); confidence in patient care in an IP team (median=4). It also stimulated student interest in IP work (median=4.5), and was an efficient use of student time (median=4.5)Conclusion: The use of HFS improved student teamwork and communication and was an accepted teaching modality. This method of exposing students of the health sciences to IP care should be incorporated throughout the curricula.